Power Awareness Experiment for Crypto Service-Based Algorithms - Toldinas, J.; Štuikys, V.; Ziberkas, G.; Naunikas, D. (Elektronika ir Elektrotechnika, 2010)
In the context of cloud computing two interrelated problems (awareness of power consumption and information safety of mobile devices) are highly important issues. The paper presents some results of experiments we have carried with 4 standard cryptography-based algorithms (AES, RC2, DES and 3DES) aiming to identify their greediness for energy, as well as to collect data for identification of relationships among various characteristics (folder size, information type, security level, algorithm type, encryption/decryption mode, performance/energy, etc.). The experiment is based on our previously developed methodology. The basic results are: 1) performance/energy characteristics are linearly dependent on the folder size and practically independent upon the information type (document or picture), 2) decryption requires much more energy resources then encryption for some class of algorithms.